The Role of Guidance Activity Units in Implementing Coaching for Female Inmates : A Study at the Class IIA Women's Detention Center Medan - Listra Agripa Sitanggang; Redyanto Sidi; Syahranuddin Syahranuddin (Law and Justice research journal, 2025)
Indonesia’s correctional system is designed not only as a form of punishment but also as a means of rehabilitation, enabling inmates to return to society as good, productive, and responsible citizens. Female inmates, however, have unique characteristics and needs compared to male inmates, requiring rehabilitation approaches that are more gender-sensitive and responsive to their conditions. This study analyzes the role of the Activity Guidance Unit in implementing rehabilitation programs for female inmates at the Class IIA Women’s Detention Center in Medan. Using a socio-legal research method with descriptive analysis, the research identifies the Activity Guidance Unit as playing a strategic and multifaceted role: acting as planner of activities, facilitator of skills training, psychosocial companion to address emotional and social needs, and evaluator of rehabilitation outcomes. The strategies applied combine holistic approaches with individual and group methods, including vocational training, counseling, and personality development programs. The results demonstrate that these integrated approaches not only improve the personal capacity of female inmates but also foster resilience, self-confidence, and readiness for social reintegration. Ultimately, the study emphasizes the importance of comprehensive and gender-sensitive rehabilitation programs as a vital component of Indonesia’s correctional system in fulfilling human rights and correctional objectives.